2019
DOI: 10.1097/htr.0000000000000544
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Occupational Therapy to an Interdisciplinary Concussion Clinic Improves Identification of Functional Impairments

Abstract: Background: Concussions, or mild traumatic brain injuries, are prevalent among youth and young adults. These injuries may disrupt a person's daily activities (occupations) including school, physical activity, work, and socialization. Rehabilitation professionals, such as occupational therapists (OTs), are experts in providing individualized intervention to address these temporary life changes during recovery. Objective: This article aims to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…To date, research suggests that telemedicine, including the use of in-person videoconferencing, is a safe, feasible, and cost-effective approach for physicians to provide initial medical assessment and follow-up care of carefully selected pediatric concussion patients living in rural and remote underserviced regions. 24,26 The role of occupational therapists in concussion management continues to expand 31,32 as does the literature suggesting a role for virtual delivery of out-patient rehabilitation to patients with neurological disorders. 33 There is also a strong body of evidence to support the delivery of virtual psychiatric services.…”
Section: Discussionmentioning
confidence: 99%
“…To date, research suggests that telemedicine, including the use of in-person videoconferencing, is a safe, feasible, and cost-effective approach for physicians to provide initial medical assessment and follow-up care of carefully selected pediatric concussion patients living in rural and remote underserviced regions. 24,26 The role of occupational therapists in concussion management continues to expand 31,32 as does the literature suggesting a role for virtual delivery of out-patient rehabilitation to patients with neurological disorders. 33 There is also a strong body of evidence to support the delivery of virtual psychiatric services.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitization to light, sound, and other sensory input may also respond well to exposure therapy as an option for those patients who have become significantly avoidant of these stimuli and have actually exacerbated their sensitivity due to this avoidant behavior [ 50 ]. Occupational therapists can also play increasing roles in concussion recovery to help patients reengage with activities that they have been avoiding, including exercise, school, and work [ 51 ].…”
Section: Multi-disciplinary Approachmentioning
confidence: 99%
“…Several observational and pilot studies have been conducted to investigate the impact of occupational therapy and various related interventions on functional improvement following TBI, though there remains significant opportunity for further study of such interventions in mild TBI specifically. First of all, including occupational therapists in the initial evaluation of patients with mild TBI has been shown to improve identification of functional impairments that may otherwise have been missed [ 95 ]. Early focus on improving executive function during acute inpatient rehabilitation following TBI has been shown to modestly improve community participation and functional independence 1 year after discharge in a heterogenous cohort of patients with complicated mild, moderate, and severe TBI [ 96 ].…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic heterogeneity of TBI makes it difficult to study, an issue further exacerbated by the limited availability of high-quality evaluation tools particularly for those with mild injuries [ 96 , 101 ]. Furthermore, there are a lack of evidence-based guidelines related to when occupational therapy should be employed in the post-TBI recovery process, leading to inconsistent referral patterns, and which techniques should be utilized, though practice recommendations have been previously published amidst these limitations (Clinical Practice Guidance: Occupational Therapy and Physical Therapy for Mild Traumatic Brain Injury, 2009) [ 95 , 102 105 ]. Recent studies, including a survey of clinicians caring for pediatric mild TBI patients, have identified that occupational therapy is routinely utilized for only a minority of patients who may benefit from it following mild TBI [ 103 , 105 ].…”
Section: Introductionmentioning
confidence: 99%